Water falls and Their Tourism Potential in Kashmir Valley, Jammu and Kashmir Region - Bilal Ahmad Bhat; Parmil Kumar; Tanzeela Habib; Ishrat Gull; Shazia Sadiq; Bilal Ahmad Zargar; Aasifa Akhter; Samira Khan; Zeenat Islam; Uzma Nazir; Mohammad Inam (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2024)
Kashmir popularly known as heaven on earth is famous for its natural beauty worldwide. The valley of Kashmir, often referred to as the “Switzerland of Asia,” is renowned for its natural beauty, and the beautiful waterfalls contribute to the region’s allure. The waterfalls have been popular tourist attractions, offering both natural beauty and opportunities for outdoor recreation. In this paper, we discusses the well-known waterfalls of Kashmir valley from a historical perspective, examining their role in tourism and their impact on the landscape development. The waterfalls in Kashmir valley usually are found mostly in higher elevations and rugged terrains,requiring construction of footpaths, narrow roads and passes to make them accessible to tourists. The survey of waterfalls revealed that tourists enjoy the visit to waterfalls but recent developments, such as power generation projects and a growing influx of visitors compromises the aesthetic value of waterfalls. It was concluded that for sustainable development, it is crucial for the government and all stakeholders to prioritize environmental protection when undertaking development projects. Balancing tourism infrastructure with ecological preservation is critical to maintain the natural beauty of these sites for future generations in view of present huge tourist flow in the study area.